PROFESSOR NA PEDAGOGIA HOSPITALAR: ATUAÇÃO E DESAFIOS - Damaris Caroline Quevedo de Melo; Vanda Moreira Machado Lima (Universidade do Oeste Paulista, 2017)
The teacher is a key element in the quest for quality education, but with a professional qualified and critically understand their role in the Brazilian educational context, essentially the Hospital Pedagogy training. This text aims to reflect on the role and challenges of the teacher to develop a qualified teacher in action teaching hospital, especially in formal education in hospital schools. The research fits into a qualitative approach, using literature and documentary research in the MEC sites and Education Department of the State of São Paulo. We found that the DCNs of Pedagogy (BRAZIL, 2006) the course form the teacher to work in school and not school, however prioritizes the training of teachers for the school environment, disregarding an area of teaching is extremely important that the hospital class. We note some challenges of teaching hospital in Pedagogy: right denied, devaluation of Hospital Pedagogy; relationship to suffering and death; pedagogue and family relationship; lack of physical infrastructure and skilled professionals.